Pain Management Knowledge of Nurses Working in Northwest Amhara Referral Hospitals in Ethiopia During 2018 - Amare Belachew Dagnew, MSC; Tilahun Tewabe, MSC (Current Therapeutic Research, 2021)
ABSTRACT: Background: Pain is an unpleasant emotional and sensory experience that is associated with actual or potential tissue damage. Providing comfort and relief of pain of clients are the fundamental role of nurses in nursing practices. However, inadequate knowledge of appropriate pain management has been reported to be a major obstacle to implementing effective pain management by nurses. Objective: The objective of this study was to assess knowledge of pain management techniques in nurses working in referral hospitals in northwest Ethiopia. Methods: An institution-based, cross-sectional, interviewer-administered questionnaire study of the pain treatment knowledge of 411 nurses was conducted in 2018 in Northwest Referral Hospitals in Ethiopia. The sample size was allocated to each selected referral hospital. A systematic sampling technique was used to select study participants. The descriptive data were presented in frequency tables. Binary and multivariable logistic regression analyses were undertaken to identify associated factors to pain management knowledge of nurses. Variables with a P value < 0.05 were considered as a significant variable. Results: Only 40.6% of nurses were judged to have had adequate knowledge regarding pain management. Number of years of training (adjusted odds ratio = 2.19; 95% CI, 1.39–3.44), prior pain education (adjusted odds ratio = 2.34; 95% CI, 1.45–3.8), and professional rank (adjusted odds ratio = 3.09; 95% CI, 1.37–6.96) were associated factors for pain management knowledge of nurses. Conclusions: The level of many nurses’ knowledge of pain management techniques were inadequate. Lack of pain training in their institution, lack of pain education in their academic curriculum, and professional rank were predictors of these nurses’ pain management knowledge. Providing pain management training and employing higher service rank nurses are likely to result in increased nurses’ knowledge of proper pain management techniques. (Curr Ther Res Clin Exp. 2021; 82:XXX–XXX)© 2021 Elsevier HS Journals, Inc.